Analysis of the human development index (HDI) with regional financial ratios approach - Prima, Yogas Andi; Faisol, Faisol; Puspita, Erna (Proceeding Kilisuci International Conference on Economic & Business, 2023)
Research Objectives: In the last three years, it has been found that there is still a significant gap in the level of welfare in the province of East Java. So the objectives of this research are try to analyze the effect of the effectiveness ratio of regional original income, regional financial efficiency ratios, and the growth of regional original income toward the human development index in East Java Indonesia. Research Method: This research used panel data regression analysis techniqueswith fixed effect model. The sample of this study included all of districts and cities in East Java. The data consists of the effectiveness ratio of regional original income, regional financial efficiency ratios, and growth of regional original income and the Human Development Index in the period of 2019 until 2021. Research Findings: Based the fixed effect model, the finding of this research are the first is the effectiveness ration does not have a positive effect on the Human Development Index in Regency and City Governments in East Java. The second is the efficiency ratio has a significant effect on the Human Development Index in Regency and City Governments in East Java,. The third is the growth of regional original income does not have a positive effect on the Human Development Index in Regency and City Governments in East Java.